(untitled) (Journal of Economic Additions, 2025)
This study examines the impact of artificial intelligence (AI) on the growth of startups in Germany. It highlights AI’s role in driving innovation in key sectors, especially healthcare and digital industries. Germany ranks among the top countries in global AI indicators. Berlin and Bavaria are identified as leading regions for AI startup activity. The industrial sector attracts the highest number of AI startups. The study finds that AI provides innovative solutions to real challenges faced by startups. These solutions support business development and long-term sustainability. Overall, AI plays a crucial role in strengthening Germany’s startup ecosystem and contributing to economic and social progress. Keywords: Startups, Artificial Intelligence, Germany. Jel Classification Codes: M13، O33، E52.